Development of Anti Acne Cream (w/o/w Multiple Emulsion) Containing Green Tea Leaf Waste - Widyaningrum, Naniek (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2017)
Background: To date, green tea leaf waste is not well utilized, the waste is remain considered as a waste. Previous studies found that green tea leaf waste still have a fairly high EGCG content. EGCG has benefits as an antibacterial. Utilization of green tea leaf waste started from formulation until the diversification of multiple emulsion w/o/w products has not been reported.Objective: To develop anti acne cream (W/O/W) multiple emulsion containing green tea leaf waste and evaluate its antibacterial activity against acne-inducing bacteria of Propionibacterium acnes (P.acnes).Methods: Phase one of this research was green tea leaves was extracted by infundation and fractionation method using ethyl acetate and prepared in different concentration (1% to 6%). The second stage was ethyl acetate fraction of green tea leaf extract was tested for its antibacterial activity against P.acnes. Third stage was tested physical properties of formulation with w/o/w multiple emulsion.Results: The optimal antibacterial activity of ethyl acetate fraction of green tea leaf extract against P.acne was at the concentration of 6%, with inhibition zone of 32.6 mm ±0.57. The formula of w/o/w multiple emulsion loaded with green tea leaves waste of 6% active substance demonstrated a good physical properties which can spread 90.4 cm2 ± 0.03, pH 5.00 ± 0.02 and microscopic analysis showed multiple emulsion w/o/w.Conclusion: The concentration of 6% green tea leaf waste formulated in multiple emulsion had a good physical and antibacterial activity for a referred standard. It is necessary to test the stability of multiple emulsion formula.